On the history of plasma treatment and comparison of microbiostatic efficacy of a historical high-frequency plasma device with two modern devices - Napp, Judith; Daeschlein, Georg; Napp, Matthias; von Podewils, Sebastian; Gümbel, Denis; Spitzmueller, Romy; Fornaciari, Paolo; Hinz, Peter; Jünger, Michael (German Medical Science GMS Publishing House, 2015)
Background: Cold atmospheric pressure plasma (CAP) with its many bioactive properties has defined a new medical field: the plasma medicine. However, in the related form of high-frequency therapy, CAP was even used briefly a century ago. The aim of this study was to review historic CAP treatments and to obtain data regarding the antimicrobial efficacy of a historical high-frequency plasma device.Methods: First, historic literature regarding the history of CAP treatment was evaluated, because in the modern literature no data were available. Second, the susceptibility of 5 different bacterial wound isolates, cultured on agar, to a historic plasma source (violet wand [VW]) and two modern devices (atmospheric pressure plasma jet [APPJ] and Dielectric Barrier Discharge [DBD]) was analyzed . The obtained inhibition areas (IA) were compared.Results: First, the most convenient popular historical electromedical treatments produced a so-called effluvia by using glass electrodes, related to today's CAP. Second, all three tested plasma sources showed complete eradication of all tested microbial strains in the treated area. The "historical" cold VW plasma showed antimicrobial effects similar to those of modern APPJ and DBD regarding the diameter of the IA.Conclusion: Some retrograde evidence may be deducted from this, especially for treatment of infectious diseases with historical plasma devices. The underlying technology may serve as model for construction of modern sucessive devices.